2011
DOI: 10.1021/ie200999h
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Ozonation of Phenol Solutions at Constant pH by Different Methods

Abstract: In this study the oxidation–reduction potential (ORP) and the proton production (Hp) profiles as a function of time were proposed as indicators to monitor the ozonation of phenol solutions at constant pH. Analysis of the ozone gas outlet stream (X O3), COD, and phenol measurements in the aqueous phase confirm the reliability of the proposed indicators. Results show that the derivative with respect to time of the normalized ozone gas outlet concentration ((1/X O30)dX O3/dt), of the oxidation–reduction potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the ozonation process, it is frequently observed that the ozone consumption rate will remarkably decrease with a rapid increase of the ORP and the reduction of pollutant removal efficiency, while the pollutant concentration goes below a certain value [48,49]. So, the ORP is a useful indicator in the control of O 3 addition, to minimize the process cost [48,50,51]. For the mineral flotation, the ORP is found to determine the oxidation of collectors and speciation of metal ions [41,44].…”
Section: Evolution Of Solution Ph Orp and Conductivitymentioning
confidence: 99%
“…In the ozonation process, it is frequently observed that the ozone consumption rate will remarkably decrease with a rapid increase of the ORP and the reduction of pollutant removal efficiency, while the pollutant concentration goes below a certain value [48,49]. So, the ORP is a useful indicator in the control of O 3 addition, to minimize the process cost [48,50,51]. For the mineral flotation, the ORP is found to determine the oxidation of collectors and speciation of metal ions [41,44].…”
Section: Evolution Of Solution Ph Orp and Conductivitymentioning
confidence: 99%
“…Several authors propose the use of oxidation–reduction potential (ORP) measurements to monitor the oxidation of several xenobiotics using advanced oxidation processes. Although ORP measurements were recently used to monitor several biological wastewater treatment processes, to our knowledge, the use of ORP to monitor an enzymatic system to remove xenobiotics has not been proposed in the literature. For this reason, in this contribution a method to of the HRP mediated oxidation of three model pollutants (orange II, phenol, and bisphenol A) with fed-batch addition of hydrogen peroxide based on ORP measurements was developed.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out at various ozone doses, and ozone consumption, mass transfer and pseudo-first order decolouration rate constants were explored. Ozone removal of five fragrance compounds in tap water and secondary effluent was and the proton production (Hp) was proposed as indicators to monitor the ozonation of phenol solution at constant pH (Contreras et al, 2011). The results indicated that ORP was effective for all testing pHs (5-11), while Hp was only useful for pH higher than 9.…”
Section: Nanotechnology Applications and Hybridmentioning
confidence: 99%